17 Reduction in left ventricular myocardial function in long-term paediatric neuroblastoma survivors. (28th September 2016) - Prendiville, T; Deery, A; Owens, C; Pears, J; Capra, M; Walsh, L; Warciak, K
Abstract : Background: There are little data on the incidence of chemotherapy-induced myocardial dysfunction in long-term survivors of high-risk (HR) neuroblastoma. Our aim was to investigate the incidence of myocardial dysfunction in patients with high-risk (HR) neuroblastoma. Method: We performed a retrospective case-control study between 2003 and 2012 of HR NBL patients treated according to the SIOPEN HR-NBL clinical trial at Our Lady's Children's Hospital, Dublin. Inclusion criteria were patients enrolled on the trial with an echocardiogram prior to commencement of chemotherapy and a subsequent echocardiogram on follow-up. Comparative echocardiograms were obtained on age-matched healthy controls. Results: 36 patients met inclusion criteria. 53% were male (n = 18). All patients received rapid COJEC induction, 83% received busulfan/melphalan (n = 30) and 61% topotecan (n = 22). 21/40 Over half received doxorubicin (n = 21). Most recent echocardiography follow-up was an average of 22 months from initial study. There was no difference in fractional shortening (FS) pre- and post-treatment (36% and 34%) (p = 0.13). Last measured FS in survivors and non-survivors (33% and 35%, respectively) was not significantly different (p = 0.18). FS in older survivors (aged 8–15) reached significance when compared to controls (p = 0.0037). There was also a significant difference between cases and age-matched controls when divided into quartiles by time since diagnosis (p = 0.079, p = 0.01, p = 0.07, p = 0.04, respectively). There was no dilation in left heart internal diameter at end diastole at any age between cases and controls. Conclusion: Reduction in left ventricular fractional shortening is seen in older patients treated for HR neuroblastoma and this finding holds true when corrected for time since diagnosis. The mechanism of ventricular dysfunction is not due to progressive dilated cardiomyopathy, as indicated by preserved left ventricular internal diameters in diastole between cases and controls. Further study is warranted.